Characteristics of Flow Development and Boiling Transitions in the Liquid Oxygen Chill-Down Process in a Straight Horizontal Exit-Contracted Pipe - Lanwei Chen; Jiaqi Zhang (International Journal of Aerospace Engineering)
Liquid oxygen chill-down in a straight horizontal pipe was studied experimentally. The effect of the entrance corner was excluded, and much denser wall temperature sensors along the pipe have been set compared to the present studies. In this way, the chill-down process, as well as the development of the flow pattern, has been drawn for every test. As a result, the mechanism of LO2 chill-down would be obtained for various pressure sections. For cases with stable pressure below 1.25 MPa, liquid rewetting in the pipe is controlled by the propagation of quenching fronts. For cases with a higher pressure, liquid rewetting in the second half of the pipe is controlled by the sudden liquid fill-in. Based on the transition points obtained, heat transfer coefficients on the Leidenfrost point and critical heat flux have been correlated for various pressure sections using new approaches. Conclusions show that the correlation equations are dependent on the chill-down mechanisms.